Strategy drives implementation: COVID vaccination in Israel - Sherry Glied (BMC, 2021)
Abstract This commentary on Rosen, Waitzberg, and Israeli's assessment of Israel's COVID response points to differences in the coherence of each national government's strategy as the key factor influencing the effectiveness of the vaccine drive. The strengths of the Israeli healthcare system facilitated implementation of the roll-out, but the government's unambiguous prioritization of vaccination drove implementation success.